Integrated physical-chemical remediation and human health risk assessment of multi-metal contaminated industrial soils - Lucia Marsich; Alessio Ferluga; Luca Cozzarini; Paolo Bevilacqua (Environmental Science and Pollution Research, 2026)
Abstract This study presents an integrated remediation strategy and human health risk assessment for multimetal-contaminated industrial soil. The sequential treatment combined mechanical screening, high-intensity magnetic separation (HIMS), and chemical extraction using ethylenediaminetetraacetic acid (EDTA). Initial characterization revealed extreme contamination levels, with cadmium and thallium posing significant noncarcinogenic risks, particularly for children (hazard index = 169.4). Physical separation proved highly effective: Mechanical screening recovered 79% of the soil mass as a cleaner coarse fraction, while HIMS achieved metal removal efficiencies between 73 and 93% for lead, arsenic, and antimony. Subsequent chemical extraction using 45 mM EDTA lowered all hazard indexes below unity for outdoor workers and residential adults. Additionally, the goal for fetal blood lead concentration (10 µg/dL) was reached after treatment with 15 mM EDTA. Despite these achievements, noncarcinogenic risks from cadmium and thallium remained above acceptable thresholds for children, indicating that the remediated soil does not yet meet the stringent requirements for residential land use without further measures. This study demonstrates that combining established physical and chemical techniques within a risk-based framework provides a practical and scientifically robust approach for managing complex multimetal soil contamination. The proposed strategy is viable for industrial or commercial redevelopment, whereas the protection of the most vulnerable populations in residential settings remains a critical challenge.